Pelatihan Pembuatan NIB dan Digital Marketing Bagi Pelaku UMKM di Moyudan - Juni Artha Siallagan; Diana Airawaty (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This service activity aims to provide an understanding of making a Business Identification Number (NIB) and the application of Digital Marketing in Micro, Small and Medium Enterprises (MSMEs). This service was carried out at Warung Soto Seger Bu Tini MSME located in Sumbersari Village, Moyudan District, Sleman Regency, Yogyakarta. This activity was carried out using observation, training and evaluation methods directly to business actors consisting of 2 stages of activities, namely Making a Business Identification Number with the Online Single Submission (OSS) system and implementing digital marketing in the use of social media, making catalogs in the Canva application and digital payments (QRIS). As a result of this activity, business actors can get a Business Identification Number as proof of an official business license and obtain legal representation guarantees, as well as an increased understanding of MSME actors in using digital tools to market their products.